ASPECTOS RELACIONADOS À APLICAÇÃO DE MICRONUTRIENTES VIA FOLIAR EM TRIGO (Triticum Aestivum L.) - Silva, Adair J. d.; Valentini, Ana P. F.; Krüger, Cleusa A. M. B.; Cadore, Pablo R.; Dambrós, Rodrigo; Silveira, Rafaela B. d.; Vezzosi, Leandro F.; Fiorin, Carlos; Carbonera, Roberto; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo